Peran Sikap Terhadap Lingkungan Pada Hubungan Antara Kemasan Keberlanjutan Dan Keputusan Pembelian Produk Avoskin Di Kota Pontianak - Della Meliska; Adi Mursalin; Puty Febriasari (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2026)
Environmental issues such as plastic waste, global warming, marine pollution, and deforestation continue to worsen and are a shared human responsibility. This study aims to analyze the effect of sustainable packaging on purchasing decisions, with attitudes toward the environment as a mediating variable. The research employed a quantitative approach with statistical data analysis to produce objective results. Findings show that sustainable packaging has a positive and significant impact on attitudes toward the environment, meaning consumers respond more positively when they perceive product packaging as sustainable. However, attitudes toward the environment were not proven to significantly influence purchasing decisions, indicating that positive views on environmental issues do not always translate into buying behavior. Conversely, sustainable packaging directly and significantly affects purchasing decisions, suggesting that packaging plays a stronger role in encouraging consumers to make purchases. Mediation analysis further confirms that attitudes toward the environment do not mediate the relationship between sustainable packaging and purchasing decisions, emphasizing that the impact of packaging is more direct and independent